2021
DOI: 10.1080/21645515.2021.1893062
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy in the era of COVID-19: could lessons from the past help in divining the future?

Abstract: Vaccine hesitancy, which embodies the unwillingness to receive vaccines when vaccination services are available and accessible, is one of the greatest threats to global health. Although vaccine hesitancy has existed among a small percentage of people for centuries, its harmful effects are likely to be more pronounced during the COVID-19 pandemic than ever before. COVID-19 vaccine hesitancy will pose substantial risks for both people who delay or refuse to be vaccinated and the wider community. It will make com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
182
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 21 publications
(49 reference statements)
5
182
0
5
Order By: Relevance
“…In this context, recently published protocols [ 13 , 14 , 15 , 19 , 20 , 22 , 23 ] and systematic literature reviews describe the importance of e-Health applied to certain healthcare contexts [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In particular, these describe how the use of online channels, instant messaging (SMS) or Short-Messages sent via apps to communicate with patients can—(i) facilitate user participation by increasing the attendance rate for health appointments [ 13 ]; (ii) tackle the misinformation prevailing on the web; (iii) improve therapeutic compliance [ 27 , 28 , 29 , 30 , 31 ]; and (iv) provide remote psychological support in patients with particular clinical conditions [ 31 , 32 ]. Conversely, digital communication tools in Public Health can act as a channel for incorrect and misleading information [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, recently published protocols [ 13 , 14 , 15 , 19 , 20 , 22 , 23 ] and systematic literature reviews describe the importance of e-Health applied to certain healthcare contexts [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In particular, these describe how the use of online channels, instant messaging (SMS) or Short-Messages sent via apps to communicate with patients can—(i) facilitate user participation by increasing the attendance rate for health appointments [ 13 ]; (ii) tackle the misinformation prevailing on the web; (iii) improve therapeutic compliance [ 27 , 28 , 29 , 30 , 31 ]; and (iv) provide remote psychological support in patients with particular clinical conditions [ 31 , 32 ]. Conversely, digital communication tools in Public Health can act as a channel for incorrect and misleading information [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the use of e-health by health institutions to counter the phenomenon of Vaccine Hesitancy and to facilitate access to services has acted as an opportunity to educate citizens towards informed and conscious health decisions [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have seen vaccine hesitancy, de ned as 'delay in acceptance or refusal of vaccination despite the availability of vaccination services in other situations across countries (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). Similar variable hesitancy rates have been reported regarding the acceptance of the COVID-19 vaccine (46,(63)(64)(65)(66). In his systematic review, Sallam (2021) found low acceptance rates in Kuwait (23.6%) and Jordan (28.4%) versus appreciably higher acceptance rates in China (91.3%), Indonesia (93.3%) and Malaysia (94.3%) (66).…”
Section: Introductionmentioning
confidence: 99%
“…Such barriers may persist and prevent uptake of the COVID-19 vaccination among patients with SLE and AAV. Other authors have similarly highlighted that past experience with other vaccines in identifying individual-level determinants of vaccine hesitancy (known as the 5C model of drivers of vaccine hesitancy, namely confidence, complacency, convenience or constraints, calculation of risk, and collective responsibility) can help focus research into COVID-19 vaccine acceptance or hesitancy and tailor strategies to address their concerns [10]. In the meantime, we eagerly anticipate more information regarding the effectiveness and safety of COVID-19 vaccination in individuals with SLE and AAV on various immunosuppressive therapies to allow physicians and patients alike to make informed decisions about COVID-19 vaccination.…”
mentioning
confidence: 99%